2003
DOI: 10.1113/jphysiol.2003.049734
|View full text |Cite
|
Sign up to set email alerts
|

The sources and sequestration of Ca2+ contributing to neuroeffector Ca2+ transients in the mouse vas deferens

Abstract: The detection of focal Ca2+ transients (called neuroeffector Ca2+ transients, or NCTs) in smooth muscle of the mouse isolated vas deferens has been used to detect the packeted release of ATP from nerve terminal varicosities acting at postjunctional P2X receptors. The present study investigates the sources and sequestration of Ca2+ in NCTs. Smooth muscle cells in whole mouse deferens were loaded with the Ca2+ indicator Oregon Green 488 BAPTA‐1 AM and viewed with a confocal microscope. Ryanodine (10 µm) decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 41 publications
2
33
2
Order By: Relevance
“…A role for transmembrane Ca 2+ influx has been implicated in this overall scheme, but the route is not known. Both Ni 2+ (50 µM) and mibefradil were ineffective in attenuating EJPs or intracellular Ca 2+ transients, suggesting that the T-type channel is not involved [67,68]. This contrasts to a study with mesenteric blood vessels, which showed the Ni 2+ did attenuate EJPs [68] and shows that similar phenomena are regulated by alternative processes in different cells.…”
Section: The Male Genitary Tractcontrasting
confidence: 51%
“…A role for transmembrane Ca 2+ influx has been implicated in this overall scheme, but the route is not known. Both Ni 2+ (50 µM) and mibefradil were ineffective in attenuating EJPs or intracellular Ca 2+ transients, suggesting that the T-type channel is not involved [67,68]. This contrasts to a study with mesenteric blood vessels, which showed the Ni 2+ did attenuate EJPs [68] and shows that similar phenomena are regulated by alternative processes in different cells.…”
Section: The Male Genitary Tractcontrasting
confidence: 51%
“…Field stimulation of the smooth muscle evoked local, transient Ca 2+ release events. These events were mediated by postsynaptic smooth muscle P2X receptors activated by ATP released from synaptic varicosities (Brain et al 2002(Brain et al , 2003. Pharmacological studies also confirmed that junctional Ca 2+ transients were mediated through the activation of purinergic receptors (Lamont and Wier, 2002;Lamont et al 2003).…”
Section: Introductionmentioning
confidence: 55%
“…The initial release occurs in the vicinity of the plasma membrane. It spreads into the cell through the regenerative release of Ca 2+ by the RyR and /or the IP3R in the form of an intracellular Ca 2+ wave travelling down the length of the cell [31][32][33]. When [Ca 2+ ]i is integrated over an entire cell with time, these Ca 2+ waves appear as rhythmical oscillations [34].…”
Section: Calcium Handling By the Sarco/endoplasmic Reticulum's Calciumentioning
confidence: 99%